Translation Techniques In The Movie Script ‘Encanto’ - Ema Yanda Sari; Mayasari Mayasari; Zuindra Zuindra (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study focuses the translation techniques in the film script Encanto. The goals of this research are to determine the types of translation procedures employed in the Encanto Movie Script, as well as to assess how these approaches are applied. Because study is conducted using sentences and clauses, the researcher employed qualitative research methodologies. The information was obtained from the Disney Hot Star App subtitle for the film